2018
DOI: 10.13057/biodiv/d190441
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoveterinary medicine and health management of Pelung Chicken in West Java, Indonesia

Abstract: Asmara IY, Garnida D, Sulisytati M, Tejaningsih S, Partasasmita R. 2018. Ethnoveterinary medicine and health managementof Pelung Chicken in West Java, Indonesia. Biodiversitas 19: 1502-1508. Pelung chicken is a race group of chickens. The spread ofPelung chicken is in the district of Cianjur, and now become widespread to several districts in West Java. The spread of Pelung chickendoes occur because as a poultry, it is attractive to people who like to keep the chicken. The chickens are mainly raised as singingc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Numerous other species can be used to stimulate appetite, including the rhizome of Curcuma aeruginosa Roxb (86.00%). This is similar to the results of Fidelity Level studies in which Zingiberaceae rhizomes were effectively used as a remedy for various digestive problems occurring in livestock, such as diarrhea, bloating, warming of the body, and anorexia more than 56% (Asmara et al 2018;Jayakumar et al 2018;Palanichamy et al 2018;Xiong and Long 2020). Observations of various livestock in India showed that the rhizome of Curcuma longa L. is also used to treat reproductive disorders, heal cracks in teats, abrasions, horn avulsion, hematomas, and blisters on the udder (Jayakumar et al 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Numerous other species can be used to stimulate appetite, including the rhizome of Curcuma aeruginosa Roxb (86.00%). This is similar to the results of Fidelity Level studies in which Zingiberaceae rhizomes were effectively used as a remedy for various digestive problems occurring in livestock, such as diarrhea, bloating, warming of the body, and anorexia more than 56% (Asmara et al 2018;Jayakumar et al 2018;Palanichamy et al 2018;Xiong and Long 2020). Observations of various livestock in India showed that the rhizome of Curcuma longa L. is also used to treat reproductive disorders, heal cracks in teats, abrasions, horn avulsion, hematomas, and blisters on the udder (Jayakumar et al 2018).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the people of West Java make use of Zingiberaceae plants such as Turmeric (Curcuma sp. ), Ginger (Zingiber officinale), and Aromatic Ginger (Kaempferia galanga L.) to also use for disease medicine in Pelung chickens (Asmara et al 2018). In Karangwangi, however, the rhizome of jahe (Zingiber officinale Roxb), cikur/kencur (Kaempferia galanga L.) and koneng/kunir (Curcuma longa L) is commonly used as a traditional supplement food, traditional medicine of bruise, gastritis, and stomach, respectively.…”
Section: Diversity Of Medicinal Plantsmentioning
confidence: 99%